Endoscopic detection of ischaemia with a new probe indicates low oxygenation of gastric epithelium in portal hypertensive gastropathy. Issue 5 (May 1995) - Piasecki, C; Chin, J; Greenslade, L; McIntyre, N; Burroughs, A K; McCormick, P A
Abstract : Changes in mucosal blood flow may be important in the pathogenesis of many conditions. Study of mucosal blood perfusion is difficult, and available methods have significant technical limitations. This study describes the development of an instrument for endoscopy, which indicates blood flow indirectly, by measuring the quantity of tissue oxygen that can diffuse from the mucosa to a luminal surface electrode. The instrument was used through an endoscope in patients with portal hypertension (n = 14), scleroderma (n = 3), disease controls (n = 7), and normal controls (n = 11). In portal hypertension readings were one quarter that in normal controls in both antrum (geometric mean (SEM) 35 (1.1)), nanoamps v 137 (1.1), and upper corpus 34 (1.1) v 125 (1.1)). Scleroderma patients showed greatly reduced oxygen readings in both antrum (18 (1.2)) and corpus (24 (1.2)), an expected but hitherto undiscovered result. These differences are highly significant (p = 0.0001), and the findings suggest that tissue hypoxia may contribute to mucosal changes in portal hypertensive gastropathy and in scleroderma.